2004
DOI: 10.1159/000080801
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary implications of pericentromeric gene expression in humans

Abstract: Human pericentromeric sequences are enriched for recent sequence duplications. The continual creation and shuffling of these duplications can create novel intron-exon structures and it has been suggested that these regions have a function as gene nurseries. However, these sequences are also rich in satellite repeats which can repress transcription, and analyses of chromosomes 10 and 21 have suggested that they are transcript poor. Here, we investigate the relationship between pericentromeric duplication and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…For example, chromatin remodeling [41] and abundance of RNA polymerase II complexes during late phases of male meiosis [42] lead to a state of “hypertranscription” [43], which may allow retrocopies to become initially transcribed in testis. This may also have facilitated transcription of new genes arising from pericentromeric segmental duplications [44,45]. Thus, there is a mechanistic bias that may favor testis expression of new genes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, chromatin remodeling [41] and abundance of RNA polymerase II complexes during late phases of male meiosis [42] lead to a state of “hypertranscription” [43], which may allow retrocopies to become initially transcribed in testis. This may also have facilitated transcription of new genes arising from pericentromeric segmental duplications [44,45]. Thus, there is a mechanistic bias that may favor testis expression of new genes.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, these genes are usually silent in normal cells, yet become expressed in some tumors and in the testis (Brun et al 2003). Microarray data on the transcription profiles of pericentromeric sequences of all human chromosomes in different tissues have been inspected in silico (Mudge and Jackson 2005). This analysis has revealed an approximate fivefold excess of transcripts specific to cancer and/or testis in pericentromeric duplications compared to the surrounding single-copy sequences, with the expression of >50% of all transcripts in duplications being restricted to these tissues.…”
Section: Duplications Genes and Pseudogenesmentioning
confidence: 99%
“…Recent studies have demonstrated the presence of active genes in recombination-suppressed chromosomal domains of mammals (Mudge and Jackson, 2005), Drosophila melanogaster (Hoskins et al, 2002), and plants (Haupt et al, 2001;Yan et al, 2005Yan et al, , 2008, which raises questions as to how the fidelity and function of such genes are maintained in an environment presumed to be void of recombination. Maintenance of structure and function of genes in the human Y chromosome has been shown to occur by intrachromatid gene conversion mediated via homologous recombination between opposing arms of large palindromic sequences (Lange et al, 2009).…”
Section: Introductionmentioning
confidence: 99%